(untitled) (Journal of Hama University, 2020)
This Study aimed to measure the Effect of interactive video recruitment in teaching the the Theoretical Side of the Curriculum of designing and producing the Educational Tools of Faculty of Education Students. The research methodology: The Semi- Experimental Method and Descriptive Analytical Approach. Were used as the appropriate method to achieve the objectives of this research. This experimental was applied during the second semester of the 2018/ 2019 years. Which has been designed: [Achievement test to measure the the Theoretical Side of the Curriculum of designing and producing the Educational Tools]. which has been applied on a random sample consists of (60) students (male & female) of the Third year of Education Techniques in the Faculty of Education at the University of Damascus. The study found the following results: There are statistically significant differences between the mean scores of the control and experimental groups in the post-application of the cognitive achievement test at the level of significance (a = 0.05) for the experimental group that studied the course using interactive video. There are statistically significant differences at the significance level (0,05) between the mean scores of experimental group in the tribal and remote applications of the cognitive achievement test at the level of significance (a = 0.05) for the benefit of the post application. There are statistically significant differences at the significance level (0,05) between the mean scores of the experimental group according to the learning strategy variable used (individual learning, cooperative) for the cooperative learning strategy.